A novel algorithm to accelerate the convergence of grand canonical Monte Carlo simulation of non-uniform fluids. Issue 4 (4th March 2017) - Zeng, Yonghong; Do, D. D.; Nicholson, D.
Abstract: A novel Monte Carlo scheme, MTZ-GCMC, utilising the 'mass transfer zone' ( MTZ ) between the fluid phase and the adsorbed phase, is proposed as an effective method for simulating the approach of a non-uniform fluid to equilibrium. We have applied this procedure to study the adsorption of gases in a closed-end graphitic slit pore, paying special attention to the region where there is a very sharp (but not vertical) condensation transition within the pore. In this region, conventional Monte Carlo ( MC ) requires a much greater computational effort to achieve convergence and may lead to incorrect results. In the MTZ-GCMC scheme, the insertion/deletion trials during the course of a simulation are restricted to the MTZ, which is identified and characterised by the percentage of successful insertions ( PSI ). Since the MTZ changes during the equilibration stage, the PSI must be updated on the fly until equilibrium has been reached. The distinct advantage of this scheme is that unnecessary insertion and deletion trials in the dense adsorbed phase, and the gas-like region are avoided; since most of these trials would be rejected, this means that convergence to the true equilibrium can be achieved an order of magnitude faster.